How Respiratory Syncytial Virus Genotypes Influence the Clinical Course in Infants Hospitalized for Bronchiolitis. (11th September 2018) - Midulla, Fabio; Nenna, Raffaella; Scagnolari, Carolina; Petrarca, Laura; Frassanito, Antonella; Viscido, Agnese; Arima, Serena; Antonelli, Guido; Pierangeli, Alessandra
Abstract : RSV NA1-infected infants had more severe bronchiolitis, while the less virulent RSV genotypes (ON1 and BA) preferentially caused bronchiolitis in infants with a possible genetic predisposition toward asthma and atopy. Abstract: Background: We aimed to study respiratory syncytial virus (RSV) genotype distribution, clinical presentation, and disease severity in infants with bronchiolitis from RSV subtypes and new RSV genotypes. Methods: We prospectively enrolled previously healthy term infants less than 1 year old hospitalized for bronchiolitis in an Italian university hospital over 12 epidemic seasons. In 312 nasopharyngeal washings positive for RSV, we sequenced the viral genotype and analyzed this according to patient data. Strain-specific RSV loads were quantified for 273 specimens. Results: From 2005–2006 to 2011–2012, the RSV-A genotype NA1 predominated, and was replaced in 2012 by the novel ON1. All infants infected with RSV subtype B were genotype BA. Stratifying data according to genotypes NA1, ON1, and BA showed that NA1-infected infants were the youngest and had the most severe clinical course. Conversely, BA-infected infants had less severe symptoms and more frequently had eosinophilia and a family history of asthma. Infants with the ON1 genotype had a milder clinical course than those with NA1 and more risk factors for asthma, despite having the highest viral loads. Conclusion: The disease course in infants hospitalized for acute RSV bronchiolitis may depend on the RSV genotype.